2003
DOI: 10.1021/ja0304852
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide−Transition-Metal Carbonyl Complexes:  New [Co4(CO)11]2-Clusters and Lanthanide(II) Isocarbonyl Polymeric Arrays

Abstract: Two types of Ln(II)-Co(4) isocarbonyl polymeric arrays, [(Et(2)O)(3)(-)(x)()(THF)(x)()Ln[Co(4)(CO)(11)]]( infinity ) (1-3; x = 0, 1) and [(THF)(5)Eu[Co(4)(CO)(11)]]( infinity ) (4), were prepared and structurally characterized. Transmetalation involving Ln(0) and Hg[Co(CO)(4)](2) in Et(2)O yields [(Et(2)O)(3)Ln[Co(4)(CO)(11)]]( infinity ) (1, Ln = Yb; 2, Ln = Eu). Dissolution of the solvent-separated ion pairs [Ln(THF)(x)()][Co(CO)(4)](2) (Ln = Yb, x = 6; Ln = Eu) in Et(2)O affords [(Et(2)O)(2)(THF)Yb[Co(4)(CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 76 publications
(95 reference statements)
1
13
0
Order By: Relevance
“…
Miscellaneous tetrasubstituted ammonium salts of [Pt 3n -(CO) 6n ]2-(n = 5-8) clusters, obtained by the stoichiometric oxidation of the corresponding [Pt 9 (CO) 18 ] 2-salts with tropylium tetrafluoroborate, self-assemble into infinite semicontinuous or continuous {[Pt 3n (CO) 3n (µ-CO) 3n ] 2-} ϱ conductor wiresOne dimensional molecular metal wires [1,2] and one-and two-dimensional superclusters that are assembled through M-M bonds [3,4] are interesting as low-dimensional molecular materials, and they may find applications in molecular electronics and nanolithography. [5][6][7] According to EHMO calculations, the LUMO of a Pt 3 (CO) 3 (µ-CO) 3 triangular moiety involves the combination of cyclopropenyl-like inphase Pt p z atomic orbitals.
…”
mentioning
confidence: 99%
“…
Miscellaneous tetrasubstituted ammonium salts of [Pt 3n -(CO) 6n ]2-(n = 5-8) clusters, obtained by the stoichiometric oxidation of the corresponding [Pt 9 (CO) 18 ] 2-salts with tropylium tetrafluoroborate, self-assemble into infinite semicontinuous or continuous {[Pt 3n (CO) 3n (µ-CO) 3n ] 2-} ϱ conductor wiresOne dimensional molecular metal wires [1,2] and one-and two-dimensional superclusters that are assembled through M-M bonds [3,4] are interesting as low-dimensional molecular materials, and they may find applications in molecular electronics and nanolithography. [5][6][7] According to EHMO calculations, the LUMO of a Pt 3 (CO) 3 (µ-CO) 3 triangular moiety involves the combination of cyclopropenyl-like inphase Pt p z atomic orbitals.
…”
mentioning
confidence: 99%
“…[1,2] To date only discrete [Pt 3n (CO) 6n ] 2À oligomers with n = 1-5 have been selectively synthesized and characterized. [2][3][4][5][6][7] 1D molecular metal wires, [8,9] and 1D and 2D superclusters [10,11] are interesting in themselves as low-dimensional molecular materials with possible applications in molecular electronics and nanolithography. [12][13][14] The recent improvement of the synthesis of "platinum carbonyl" [7] prompted a reinvestigation of the chemistry of the [Pt 3n (CO) (CO) 48 ] reveals a distribution of oligomers centered at n = 5, with peaks of lesser intensity at n = 4 and n = 6.…”
mentioning
confidence: 99%
“…[5 -9] Research has been focused on the elucidation of the interaction between the two metals, and little is known concerning the application of these compounds as catalytic and magnetic materials, although it was suggested that complexes containing Ln-M carbonyls offer the possibility of functioning as catalyst precursors [10 -13] . Until now, the determination of the structural relationship between the two metals has revealed three possible structure types of Ln-M complexes: [14] ion pairs (I), isocarbonyl linkages (II) and Ln-M direct bonds (III), for example, [Ln 9 (OH) 10 (acac) 16 ][HCr 2 (CO) 10 ] (Ln = Sm, Eu, Gd, Dy, Yb) (I), [15] [Yb(THF) 6 ][Co(CO) 4 ] 2 (I), [16] [(THF) 4 I 2 Sm(µ-OC)Mo(CO) 2 (C 5 H 5 )] (II), [17] [(Pry) 4 Yb{(µ-OC) 2 − Co(CO) 2 } 2 ] ∞ (II), [14] {[(CH 3 CN) 3 YbFe(CO) 4 ] 2 CH 3 CN} ∞ (III) [18] and [(NH 3 ) 3 YbFe(CO) 4 ] (III). [19] However, these assorted Ln-M interactions influence the assembly of the compounds, the distance between lanthanide and transition metal is not easy to control and discrete molecules or polymeric arrays were encountered.…”
Section: Introductionmentioning
confidence: 99%
“…[19] However, these assorted Ln-M interactions influence the assembly of the compounds, the distance between lanthanide and transition metal is not easy to control and discrete molecules or polymeric arrays were encountered. [14] In light of their potential applications and their diverse structural motifs, we are interested in synthesizing a new type of heterobimetallic carbonyl compounds, which contains organic functional groups as bridging ligands. The carbonyl cluster fragment we have chosen is the well-known capped tricobalt (CO) 9 Co 3 C, which is both a versatile electronic donor and acceptor, [20] while the functional group we have chosen is [-COO] − , which has the ability to coordinate to Ln(III) cores.…”
Section: Introductionmentioning
confidence: 99%